Cognitive status predicts preoperative instruction compliance - Mano, Yasuko; Mistry, Porus; Tran, Khoa; Wright, Benjamin; Malekyan, Cristin; Gurvich, Tatyana; Kaloostian, Carolyn; Motamed, Arash; Decker, Justyne (Frontiers in Aging Neuroscience, 2023)
The most common postoperative complication for older adults is perioperative neurocognitive disorder (PNCD). 1,2 Its greatest risk factor is preoperative cognitive impairment.1-3 Cognitive impairment also predicts higher likelihood of postoperative complications.3 While the cause of disparity in outcomes is likely multifactorial, the ability to correctly follow perioperative instructions may be one modifiable component. The purpose of this study was to determine whether cognitive impairment led to reduced preoperative instruction compliance and if so, identify barriers and enact a tailored care-plan to close the gap. Our preoperative clinic implemented routine Mini-Cog screening to identify older (age >65) surgical patients at increased risk. All patients received the same instructions and, on day of surgery, were surveyed to determine correct execution of NPO guidelines, chlorhexidine wipe use and medication management. Data was stratified by cognitive status to evaluate whether impairment predicted instruction execution. Feedback from patients and families were compiled. Of those who screened negative for impairment, 68% correctly followed instructions, while 84.2% of those impaired struggled with >1 instruction(s); impaired patients were more likely to incorrectly follow instructions (OR 10.5, p-value 0.001). Areas for change were identified and team-based solutions were enacted with additional support for those with impairment. We found a clear difference in correct execution with respect to cognitive status. By improving instructions as an institution and adding additional support for those with impairment, the compliance gap was significantly reduced. Targeting perioperative instructions and tailoring care in this population may be one modifiable component in the outcome disparity they face.